Digital Landscape Design for Infrastructure Business on Islamic Financial Technology Platforms in Indonesia - Bayu Wardhana (BASKARA : Journal of Business and Entrepreneurship, 2022)
The trend of digitization is a phenomenon that is quite popular in recent years where this phenomenon has entered all sectors, including the financial sector. The emergence of financial technology innovation is evidence that the digitalization phenomenon has entered the financial and banking sectors. Therefore, this innovation is not only present to provide financial services, but must be able to provide solutions, especially for micro, small and medium businesses as a fintech business segment. The research method used in this study is a descriptive qualitative approach. The results of the research produced are designing the structure of fintech application features to answer the problems that occur in MSMEs